2023
DOI: 10.1002/qua.27234
|View full text |Cite
|
Sign up to set email alerts
|

Topological indices and QSPR analysis of some chemical structures applied for the treatment of heart patients

Mehri Hasani,
Masoud Ghods

Abstract: In this study, various beta‐blocker drugs used for heart disease were analyzed, and their degree‐based topological indices derived from the M‐polynomial were calculated. Linear and quadratic regression analysis was used to obtain quantitative structure‐property relationship models between the topological indices and eight the physicochemical properties of the drugs to determine their effectiveness. The results show that the harmonic index was the best predictor for boiling point, flashpoint, and enthalpy of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…They suggested that an index would be meaningful if it could accurately describe at least one property. For some recent works on this concept, readers are referred to [28–43]. Initially, octane isomers are used as a reference dataset for such investigation.…”
Section: Chemical Relevancementioning
confidence: 99%
“…They suggested that an index would be meaningful if it could accurately describe at least one property. For some recent works on this concept, readers are referred to [28–43]. Initially, octane isomers are used as a reference dataset for such investigation.…”
Section: Chemical Relevancementioning
confidence: 99%
“…Hasani et al [10] investigated the effectiveness of various beta‐blocker drugs used for heart disease using the QSPR model between the topological indices and the physico‐chemical properties of drugs. Arockiaraj et al [11] developed a QSPR model using distance‐based topological indices for anti‐tuberculosis medications and studied their diverse physicochemical features.…”
Section: Introductionmentioning
confidence: 99%
“…QSPR modeling employs graph theory to predict a drug's properties based on its molecular structure. Researchers develop QSPR models using statistical and mathematical methods to quantify the relationship between the molecular structure and the properties of interest [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%